Engineering Applications of Neural Networks 13th International Conference, EANN 2012, London, UK, September 20-23, 2012. - Jayne, Chrisina; Yue, Shigang; Iliadis, Lazaros S. (Communications in Computer and Information Science, 2012)
This book constitutes the refereed proceedings of the 13th International Conference on Engineering Applications of Neural Networks, EANN 2012, held in London, UK, in September 2012. The 49 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers describe the applications of neural networks and other computational intelligence approaches to intelligent transport, environmental engineering, computer security, civil engineering, financial forecasting, virtual learning environments, language interpretation, bioinformatics and general engineering.